Caracterización del sistema productivo de los Bovinos en el Centro de Experimentación Académica Salache (CEASA). - Simbaña Cifuentes, Jonathan Fabricio (2019)
This research was carried out in the Salache Academic Experimentation Center (CEASA) belonging to the Technical University of Cotopaxi, which is located in Cotopaxi province, Latacunga canton, Eloy Alfaro parish; Salache Bajo neighborhood and whose geographic location is 00 ° 59 '57 "north latitude and 78 ° 37' 14 '' west longitude, at 2725 height meters above sea level. The cattle herd composed of 33 animals of the Holstein Friesian and Criollo Pizán breeds, their grazing area and their meteorological conditions were characterized. Regarding cattle, a categorization was made and evaluated: milk production, animal load, load potential, energy requirement, nutritional balance in relation MS-EM-protein-minerals, fat percentage at milk, BUN and MUN. With reference to the pastures, bromatological analyzes of the forages were carried out, determining the percentage of: MS, NDF, and protein and minerals. With regard to the soil component, soil analysis was carried out determining: pH, cation exchange capacity, nutrient availability. The variables were analyzed in a livestock management template in Excel, obtaining as a result a deficit of 32,454.27 Mcal of ME and 683.77 kg of DM in bovines. The meteorological data showed a rainfall deficit with a minimum of 10 mm and a maximum of 75 mm, being 120 mm / water / m2 the monthly requirement to obtain optimum growth rates of 65 Kg of DM per day. These results were oriented to establish recommendations that will contribute to improve CEASA's productive indexes